The relationship between the employees' perceptions of CSR, work engagement and human values - Pereira, A. (2016)
In a business context, the reciprocal influence established between employees engaged in the performance of the organization and the effects of certain practices and policies adopted by the company in employees’ attitudes and behaviours is clear. This research focuses on possible relationships between the employees’ perceptions of Corporate Social Responsibility (CSR), the work engagement and human values. The study is inspired by the European perspective of CSR and by the Cohen’s approach (2010). The work engagement dimensions were identified following the perspective of Schaufeli and Bakker (2003). For the human values, the model of Schwartz (1999) was used. A questionnaire was applied to a sample of 257 employees. The main results suggest that work engagement dimensions are explained by the employees’ perceptions of CSR in its dimensions of marketplace and workplace, being themselves mediator variables between age and seniority and the work engagement dimension of dedication/vigour.